Reducing meat consumption through default nudging: a field study - Ardesch, Tamar F.; Klaperski-van der Wal, Sandra; Nijssen, Sari R. R.; Müller, Barbara C. N. (Frontiers in Psychology, 2025)
Meat consumption negatively impacts ecological sustainability, health, and animal welfare. Research suggested promising effects of re-designing product arrangements so that vegetarian items become the default. However, whether default nudging leads to actual behaviour change in the context of meat consumption, and whether these effects are sustainable on the long-term remains unknown. Therefore, this field experiment investigated (a) the effect of vegetarian default nudging on food choices in a real-life setting, and (b) potential long-term associations between vegetarian defaults, food choices, and psychological resistance (i.e., reactance and inertia). A vegetarian default intervention was applied in a university cafeteria. Behavioural data (cafeteria sales data regarding meat and vegetarian purchases; N = 4,099) was collected before (T0; baseline), right after implementation (T1), and 10 weeks after implementation of the intervention (T2). Additionally, survey data was collected at T1 and T2 to assess potential psychological side-effects, such as resistance to the intervention. Results indicate that vegetarian default nudging was highly effective at changing food choices, with more than twice the number of vegetarian items sold relative to baseline. Moreover, in the default nudging condition, the number of meat items decreased to less than a third of the baseline measurement. At the same time, the survey data revealed no psychological side-effect of the intervention on reactance or inertia. This was stable over time. Our research offers empirical support for the effectiveness of a non-coercive strategy to change consumer behaviour towards more sustainable, animal friendly, and healthier food choices.